Assessment of heavy metal contamination in surface sediments in the western Taiwan Strait. (October 2020) - Zhai, Bin; Liu, Zhaoqing; Wang, Xianchao; Bai, Fenglong; Wang, Libo; Chen, Zhengxin; Zhang, Xilin
Abstract: The concentrations of the heavy metals Cu, Pb, Zn, As, Cr, Co, and Ni of a total of 187 surface sediment samples collected from the western Taiwan Strait were analyzed. The distribution characteristics and degree of contamination of these elements were investigated. The mean concentrations of Cu, Pb, Zn, As, Cr, Co, and Ni in the surface sediments of the study area were 10.2 mg/kg, 18.3 mg/kg, 51.7 mg/kg, 7.5 mg/kg, 38.7 mg/kg, 8.0 mg/kg, and 16.5 mg/kg, respectively. The heavy metals in the study area were mainly from natural sources. The regional pollution load index (PLIzone) was 0.64, indicating that there was no contamination, and an area with a relatively high PLIzone was found in the northern part of the study area. Furthermore, the impacts of the rapid development of Fujian's marine economy on the marine environment in the past decade should be further compared and analyzed. Highlights: The concentrations of the heavy metals were analyzed on the western Taiwan Strait. The distribution characteristics and degree of contamination were investigated. The regional pollution load index indicated that there was no contamination. Relatively high PLIzone was found in the northern part of the study area. The contamination of the northern area should be continuously monitored.